SOCIAL MEDIA, ISLAMIC FINANCIAL LITERACY, AND ISLAMIC BANKING PRODUCT OWNERSHIP: A MODERATING MODEL - Lutfi Lutfi; Vita Prihatiningrum (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The role of social media and Islamic financial literacy is critical in influencing the consumer to have Islamic financial products. However, no studies on this topic have been conducted in Indonesia. The use of social media by a millennial is snowballing. This study examines the impact of social media, represented by the attractiveness of influencers and social media engagement, on the intention to own Sharia banking investment products among the millennial generation. This study also examines the role of Islamic financial literacy and income as independent and moderating variables. Data is collected using purposive sampling, followed by convenience sampling through a Google form questionnaire distributed to the social media users of Gen Z in the Surabaya agglomeration area. This study used 216 questionnaires and analyzed them using Partial Least Square - Structural Equation Model (PLS-SEM). The results show that influencer attractiveness, social media engagement, and Sharia financial literacy positively influence millennials' ownership intention of Islamic banking investment products. Islamic financial literacy weakens influencer attractiveness's impact on the ownership intention of Islamic banking investment products, while income does not moderate the relationship. Furthermore, social media engagement is most significant in determining product ownership intentions. The practical implication of the findings suggests the importance of Islamic banks to encourage more engagement of their social media users by providing useful information about bank products. This research provides a theoretical contribution to the theory of consumer behavior and social media that using social media is one of the most effective ways of influencing consumer purchasing decisions.